2023
DOI: 10.3389/fmicb.2022.1090392
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of gut mycobiota profiles in intrahepatic cholangiocarcinoma

Abstract: ObjectiveIntrahepatic cholangiocarcinoma (ICC) is a silent liver malignancy with an increasing incidence. Gut mycobiota plays a crucial role in benign liver diseases; however, its correlation with ICC remains elusive. This study aimed to elucidate fungal differences in patients with ICC compared to healthy controls.MethodsThe 40 fecal samples from 23 ICC patients and 17 healthy controls were collected and analyzed using ITS2 rDNA sequencing. Obtaining the OTUs and combining effective grouping, we carried out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…[55] cultivation -n. s. carriers of Salmonella typhi and Salmonella paratyphi had a large excess of cancer mortality, particularly of gallbladder carcinoma (compared to non-carriers) [48] 16s RNA (V4) n. s. recently none in case of venous infiltration ↑ family Oscillospiraceae and ↓ family Eubacteriaceae, genera Allobaculum, Pediococcus, Pseudoramibacter, Peptostreptococcus [54] 16s RNA (V4) -none treatment with neomycin for elimination of Gram-negative bacteria resulted in fewer CCA, after dysbiotic fecal microbial transplantation germ-free mice developed liver myeloid cell accumulation, which is associated with worse outcome of CCA [52] sequencing, n. s. n. s. none for at least 3 months ↑ species Lachnospiraceae bacterium-GAM79, Erysipelotrichaceae bacterium-GAM147, Ruminococcus callidus, Alistipes megaguti and Bacteroides zoogleoformans => longer PFS and OS; ↑ family Veillonellaceae => shorter PFS and OS In biliary tract cancer patients: ↑ order Bacteroidales => longer PFS and OS, ↑ family Veillonellaceae = shorter PFS and OS [51] ITS2 rDNA before treatment none for at least 3 months 3) investigated the association between the gut microbiota and the oncological outcome of unresectable HCC and advanced biliary tract carcinoma [52]. Survival analysis revealed longer progression-free survival (PFS) and overall survival (OS) in patients with a higher abundance of species Lachnospiraceae bacterium-GAM79, Erysipelotrichaceae bacterium-GAM147, Ruminococcus callidus, Alistipes megaguti and Bacteroides zoogleoformans.…”
Section: Ref Methods Time Point Antibiotics or Probiotics Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[55] cultivation -n. s. carriers of Salmonella typhi and Salmonella paratyphi had a large excess of cancer mortality, particularly of gallbladder carcinoma (compared to non-carriers) [48] 16s RNA (V4) n. s. recently none in case of venous infiltration ↑ family Oscillospiraceae and ↓ family Eubacteriaceae, genera Allobaculum, Pediococcus, Pseudoramibacter, Peptostreptococcus [54] 16s RNA (V4) -none treatment with neomycin for elimination of Gram-negative bacteria resulted in fewer CCA, after dysbiotic fecal microbial transplantation germ-free mice developed liver myeloid cell accumulation, which is associated with worse outcome of CCA [52] sequencing, n. s. n. s. none for at least 3 months ↑ species Lachnospiraceae bacterium-GAM79, Erysipelotrichaceae bacterium-GAM147, Ruminococcus callidus, Alistipes megaguti and Bacteroides zoogleoformans => longer PFS and OS; ↑ family Veillonellaceae => shorter PFS and OS In biliary tract cancer patients: ↑ order Bacteroidales => longer PFS and OS, ↑ family Veillonellaceae = shorter PFS and OS [51] ITS2 rDNA before treatment none for at least 3 months 3) investigated the association between the gut microbiota and the oncological outcome of unresectable HCC and advanced biliary tract carcinoma [52]. Survival analysis revealed longer progression-free survival (PFS) and overall survival (OS) in patients with a higher abundance of species Lachnospiraceae bacterium-GAM79, Erysipelotrichaceae bacterium-GAM147, Ruminococcus callidus, Alistipes megaguti and Bacteroides zoogleoformans.…”
Section: Ref Methods Time Point Antibiotics or Probiotics Resultsmentioning
confidence: 99%
“…A simplified overview of differences in gut microbial composition of CCA patients compared to healthy controls is shown in Figure 4. The entire composition of gut microbiota of CCA patients compared to healthy controls was investigated in seven studies [45][46][47][48][49][50][51]. The results of diversity indices were inhomogeneous.…”
Section: Gut Microbiota Changes In Cca Patientsmentioning
confidence: 99%
“…Simultaneously, the gut microbiota and its metabolites are transported to the liver through the bile duct. Therefore, the gut microbiota plays a pivotal role in the pathogenesis and progression CCA[ 18 , 35 ]. Hence, there is a compelling need for additional investigations to elucidate the causal connection between gut microbiota and CCA, thereby establishing a novel theoretical foundation for the prevention and treatment of CCA.…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota actively fosters the development of extraintestinal cancers by facilitating bacterial translocation and the generation of bioactive molecules within the biliary tract. Numerous research investigations have demonstrated notable distinctions in gut microbiota composition between individuals with extraintestinal cancers and those without the disease[ 32 , 35 ]. Bacteroides and Ruminococcaceae have been shown to potentially contribute to the pathogenesis of hepatocellular carcinoma by exacerbating hepatic inflammation, accumulating toxic compounds, and inducing liver steatosis[ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging views suggest that the gut virome plays a vital role in regulating homeostasis and disease progression through interactions with the bacteriome and the human immune system [7]. These studies have revealed significant associations between changes in phage composition and several diseases [8][9][10][11], such as metabolic syndrome [12,13], necrotizing enterocolitis [14], inflammatory bowel disease [15][16][17][18], and type two diabetes mellitus [19,20]. Recent cross-cohort meta-analyses have identified specific gut viral biomarkers, such as phages of Porphyromonas, Fusobacterium, and Hungatella, enriched in colorectal cancer patients, suggesting their potential as treatment targets [21].…”
Section: Introductionmentioning
confidence: 99%